2005
DOI: 10.4049/jimmunol.174.12.7584
|View full text |Cite
|
Sign up to set email alerts
|

Tetrahydro-4-Aminobiopterin Attenuates Dendritic Cell-Induced T Cell Priming Independently from Inducible Nitric Oxide Synthase

Abstract: Formation of NO by NO synthases (NOSs) strictly depends on tetrahydrobiopterin. Its structural analog, tetrahydro-4-aminobiopterin, is an inhibitor of all NOS isoenzymes, which prolongs allograft survival in acute murine cardiac rejection and prevents septic shock in the rat. In this study, we show that murine bone marrow-derived dendritic cells treated with tetrahydro-4-aminobiopterin had a reduced capacity to prime alloreactive murine T cells in oxidative mitogenesis. Checking for a possible influence on LPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…This suggests that the tetrahydrobiopterin compounds may exert their effect primarily on the posttranscriptional level. Consistent with this suggestion we found that in cultured murine bone marrow derived dendritic cells 4-amino tetrahydrobiopterin suppresses expression of MHC class II antigen and T-cell stimulatory capacity without affecting MHC class II mRNA levels in the cells (33). Interestingly, these effects were even more pronounced in cells from iNOS (-,-) mice (33).…”
Section: Discussionsupporting
confidence: 84%
“…This suggests that the tetrahydrobiopterin compounds may exert their effect primarily on the posttranscriptional level. Consistent with this suggestion we found that in cultured murine bone marrow derived dendritic cells 4-amino tetrahydrobiopterin suppresses expression of MHC class II antigen and T-cell stimulatory capacity without affecting MHC class II mRNA levels in the cells (33). Interestingly, these effects were even more pronounced in cells from iNOS (-,-) mice (33).…”
Section: Discussionsupporting
confidence: 84%
“…This does not exclude the possibility that sepiapterin improved rejection by some other redundant gene pathway. An intriguing possibility for the antirejection mechanism of sepiapterin is via an effect on T-cell function (Thoeni et al, 2005). In this context, we showed that sepiapterin decreased IL-2 expression, an important product of T-cell activation and a growth factor for T cells.…”
mentioning
confidence: 81%
“…ABH 4 could effectively induce apoptosis in T cells as well as in murine macrophages [21,50]. Our data demonstrate that high concentrations of ABH 4 present for longer periods of time cause a significant amount of cell death in HL-1 cardiomycoytes.…”
Section: Discussionmentioning
confidence: 84%
“…Inhibition of iNOS, however, did not account for the aforementioned protective effects of ABH 4 seen during acute rejection, as these occurred independently of the iNOS-inhibitory effect of ABH 4 [14]. Additionally, ABH 4 exhibited immunosuppressive effects, which did not relate to the iNOS-inhibiting properties of the compound either [21].…”
Section: Introductionmentioning
confidence: 93%